TEACHER TRAINING: MAKING COGNITIVE AND MOTOR STIMULATION GAMES FROM USED MATERIALS: Pelatihan Guru: Membuat Permainan Stimulasi Kognitif Dan Motorik Dari Bahan Bekas - mariyati, lely; Maulana , Muhammad Asrul; Sofy, Ayu; Suhermanto , Suhermanto; Ramadhan , Gilang (Journal of Social Comunity Services, 2024)
Stimulation of early childhood development varies widely, from expensive methods to utilizing recycled materials. The stimulation of early childhood development at TK Bustanul Athfal Ketegan Sidoarjo is still relatively limited. The goal of this activity is to enhance the cognitive and motor skills of young children and improve the educators' skills at TK Bustanul Athfal Ketegan Sidoarjo by creating stimulation play media using recycled materials as a tool for early childhood learning. The method for this activity includes presentations and training for educators on how to create cognitive and motor development stimulation media for children using recycled materials, as well as engaging in role-playing activities to utilize these stimulation media. The benefits of this activity include expanding the variety of learning media and enhancing the knowledge and skills of educators at TK Bustanul Athfal Ketegan Sidoarjo in creating learning stimulation media for their students using recycled materials. While a small portion of the teachers has not fully understood APE (Early Childhood Stimulation), 90% have comprehended the effective methods of creating and applying APE block number and APE Flashcard